Evidence of the Beginning of Islam in Sumatera: Study on the Acehnese Tombstone - Suprayitno, Suprayitno (TAWARIKH, 2011)
ABSTRACT: Acehnese tombstone is a unique terminology of a work of art involves the art design, calligraphy, and literature on a stone. The terminology was first appeared in the second decade of the 20th century. Preliminary assessment on the tombstone is still concentrated on the relationship between status of the death figure (sacred tomb) and the burial customs of the Malays/Muslims. After Indonesia independence (1945), some archeologists and historians began to analyze the Acehnese tombstone, including basic shapes, calligraphy, class, typology, and chronology of the use of Acehnese tombstones. Through a careful study of the Acehnese gravestones, it is to open the curtain on the process of Islamization in Indonesia or in Southeast Asia. Findings Acehnese tombstone dating 1007 AD in Lamreh village, Aceh Besar, two hundred years earlier than the tomb of Malik al-Saleh in Pasai, proving that the stone grave marker of Aceh has been used since the early 11th century AD and Islam has been present in Sumatera or Indonesia since the beginning of the 11th century AD.KEY WORDS: Acehnese tombstone, Lamreh village, typology, chronology, and process of Islamization in Indonesia.About the Author: Dr. Suprayitno is a Lecturer at the Department of History, Faculty of Letters USU (University of North Sumatera), Jalan Universitas No.19, USU Campus, Padang Bulan, Medan, North Sumatera, Indonesia. He can be reached at: praitno@yahoo.comHow to cite this article? Suprayitno. (2011). âEvidence of the Beginning of Islam in Sumatera: Study on the Acehnese Tombstoneâ in TAWARIKH: International Journal for Historical Studies, Vol.2(2) April, pp.125-146. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 11, 2011); Revised (March 15, 2011); and Published (April 28, 2011).